FAKTOR FAKTOR YANG MEMPENGARUHI KEBIJAKAN DEVIDEN DENGAN KEPUTUSAN INVESTASI SEBAGAI VARIABEL MODERATING - Elly Susanti; Liper Siregar (Jurnal Akuntansi dan Pajak, 2023)
The purpose of this study is to identify factors affecting dividend policy (liquidity leverage and profitability) and to identify and analyze whether investment decisions can strengthen or weaken the effect of liquidity leverage and profitability on dividend policy. The study was conducted in the years 2016-2020 in the Food and Beverage sub-sector company and the sample was conducted by purposive sampling. Data analysis techniques include classical estimation testing hypothesis testing and residual testing. The results of this study partially show the hypothesis that liquidity has a significant positive effect leverage has a positive but insignificant effect and profitability has a significant negative effect on dividend policy while all variables (liquidity and profitability) have a significant effect. Positive effect. Investment decisions do not amplify the effects of liquidity and profitability on dividend policy